Peran Manajerial Kepala Sekolah dan Partisipasi Masyarakat dalam Implementasi Kurikulum Merdeka di SDN Gunung Picung 07 Pamijahan Bogor - Esa Hari Wibowo; Yusi Srihartini; Ika Kartika (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research examines the managerial role of the school principal and community participation in the implementation of the Independent Curriculum at SDN Gunung Picung 07 Pamijahan, Bogor. This research aims to identify the impact of the school principal's managerial role and community involvement on the success of curriculum implementation. With a qualitative approach, data is collected through observation, interviews and documentation, and analyzed inductively using triangulation techniques to ensure validity. The research results show that the managerial role of the school principal and community participation, including parental involvement and the Foster Friends Movement (GERTA) program, play an important role in the successful implementation of the Independent Curriculum. The successful implementation of this curriculum depends on strong principal management, active community participation, as well as support and innovation in teaching methods, which overall support effective curriculum implementation and bring positive change in education.